Downregulation of miRNA miR-1305 and upregulation of miRNA miR-6785-5p may be associated with psoriasis - Yan, Jianjun; Zhen, Yunyue; Wang, Ruijie; Li, Xueqing; Huang, Shan; Zhong, Hua; Wen, He; Sun, Qing (Frontiers in Genetics, 2022)
Background: The role of serum extracellular vesicles (EVs) is less known in psoriasis. Objectives: To explore the transcriptomic profile of serum EVs and the potential biomarkers in psoriasis. Methods: EVs were isolated by differential ultracentrifugation and identified by transmission electron microscope. The diameters of EVs were detected using nanoparticle tracking analysis. Serum EVs-keratinocyte interaction was observed through confocal fluorescence microscopy. miRNA microarray and mRNA microarray were performed in serum EVs (n=4) and skin lesions (n=3), respectively. Quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) and fluorescence in situ hybridization were used to detect the expression of miRNAs in serum EVs and skin lesions (n=15). Bioinformatics analysis was performed to predict the potential target genes and functions of miR-1305 and miR-6785-5p. Western blot, CCK-8 and enzyme-linked immunosorbent assay (ELISA) were used to detect the EVs’ biomarkers, keratinocytes proliferation and cytokines secretion. Results: A total of 16 miRNAs and 1,725 mRNAs were significantly dysregulated in serum EVs and skin lesions, respectively. miR-1305 was down-regulated and miR-6785-5p was up-regulated in both serum EVs and skin lesions. Serum EVs could be taken up by keratinocytes. miR-1305 was down-regulated and miR-6785-5p were up-regulated in keratinocytes after co-cultured with psoriasis serum EVs compared with controls. Psoriasis serum EVs promoted keratinocyte proliferation and the secretion of CCL20 and IL-8. Serum EVs miR-1305 and miR-6785-5p were associated with disease severity. Conclusions: Serum EVs might be involved in the activation of keratinocytes through loaded miRNAs in psoriasis. Serum EVs miR-1305 and miR-6785-5p may be associated with psoriasis.